PENGEMBANGAN BUKU CERITA BERGAMBAR TENTANG MITIGASI BENCANA ERUPSI GUNUNG API UNTUK SISWA SD - Suryaningsih, Eni; Fatmawati, Laila (Profesi Pendidikan Dasar, 2017)
The background of this research is fact in the field regarding low knowledge of the community about disaster mitigation. Besides, there is no knowledge material presentation about volcano eruption disaster mitigation that routinely scheduled at schools in disaster prone areas. A media is needed to deliver knowledge material about mitigation and can be integrated in learning. This research aims to develop and determine the feasibility of picture story books about volcano eruption disaster mitigation for elementary school students in disaster prone areas. This is a Research and Development which carried out eight stages. The result of the assessments from the media expert is 85.33 (very good), material expert is 89.6 (very good), language expert is 76 (good), product test is 95.08 (very good), and application test is 88.66 (very good). All assessments average score is 86.93 converted into qualitative data is in the category of "Very Good".